Nitric oxide releasing vascular catheters for eradicating bacterial infection. Issue 8 (20th December 2017) - Pant, Jitendra; Goudie, Marcus J.; Chaji, Sarah M.; Johnson, Benjamin W.; Handa, Hitesh
Abstract: The interaction of blood proteins with an implant surface is not only a fundamental phenomenon but is also key to several important medical complications. Plasma proteins binding on the surface of intravascular catheters can promote bacterial adhesion leading to the risk of local and systemic complications such as catheter‐related blood infections (CRBIs). The incidences of CRBIs in the United States amount to more than 250, 000 cases/year with an attributable mortality of up to 35% and an annual healthcare expenditure of 2.3 billion approximately. This demands the development of truly nonthrombogenic and antimicrobial catheters. In the present study, catheters were fabricated by incorporating a nitric oxide (NO) donor molecule, S ‐nitroso‐ N ‐acetyl‐penicillamine (SNAP) in a hydrophobic medical grade polymer, Elasteon‐E2As. NO offers antithrombotic and antibacterial attributes without promoting drug resistance and cytotoxicity. E2As‐SNAP catheters were first coated with fibrinogen, a blood plasma protein plays a key role in clot formation and eventual bacterial adhesion to the implant surface. The suitability of the catheters for biomedical applications was tested in vitro for contact angle, NO release kinetics, inhibition of bacteria, and absence of cytotoxicity toward mammalian cells. The highly hydrophobic catheters released NO in the physiological range that inhibited >99% bacterial viability on fibrinogen‐coated catheters in a 24 h study. No toxic response of E2As‐SNAP catheters leachate was observed using a standard cytotoxicity assay with mouse fibroblast cells. Overall, the results showed that the E2As‐SNAP catheters can inhibit viable bacteria even in the presence of blood proteins without causing a cytotoxic response. The fundamentals of this study are applicable to other blood‐contacting medical devices as well. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2849–2857, 2018.